THE THEORY OF MONETARISM AND KEYNESIANISM, THEIR PRACTICAL SIGNIFICANCE IN THE PRESENT ERA - Normamatov Farrukh Bakhtiyorovich (American Journals, 2023)
This article examines the emergence of Monetarist and Keynesian theories and their theoretical and practical significance. The main directions of the Keynesian theory and their characteristics,the analysis of the conflicting aspects with the theory of monetarism was carried out. In addition, the practical importance of the theory of monetarism in the current period and the experience of foreign countries in the effective use of monetary policy instruments are mentioned. The directions of effective use of monetary policy have been highlighted.
Keywords: employment rate, monetary policy, financial instruments, economic crisis. Keynesianism, economic growth, inflation, unemployment, money supply, budget deficit, fiscal policy, investment.